2007
DOI: 10.1128/aac.01009-06
|View full text |Cite
|
Sign up to set email alerts
|

Addition of a C-Terminal Cysteine Improves the Anti-Herpes Simplex Virus Activity of a Peptide Containing the Human Immunodeficiency Virus Type 1 TAT Protein Transduction Domain

Abstract: Previous studies have shown that peptides containing the protein transduction domain (PTD) of the human immunodeficiency virus tat protein (GRKKRRQRRR) were effective inhibitors of herpes simplex virus type 1 (HSV-1) entry (H. Bultmann and C. R. Brandt, J. Biol. Chem. 277:36018-36023, 2002). We now show that the addition of a single cysteine residue to the C terminus of the TAT PTD (TAT-C peptide) improves the antiviral activity against HSV-1 and HSV-2. The principle effect of adding the cysteine was to enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…The cationic ␤-peptides are also likely to bind to heparan sulfate, raising the question of why the cationic ␤-peptides do not block attachment. In our studies with TAT peptides, we found that attachment was not inhibited to a significant extent, suggesting that TAT peptides and HSV-1 recognize different structural features in heparan sulfate (9). Thus, it is possible that the cationic ␤-peptides act similarly to TAT and therefore do not inhibit attachment of the virus to cells.…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…The cationic ␤-peptides are also likely to bind to heparan sulfate, raising the question of why the cationic ␤-peptides do not block attachment. In our studies with TAT peptides, we found that attachment was not inhibited to a significant extent, suggesting that TAT peptides and HSV-1 recognize different structural features in heparan sulfate (9). Thus, it is possible that the cationic ␤-peptides act similarly to TAT and therefore do not inhibit attachment of the virus to cells.…”
mentioning
confidence: 65%
“…In addition to inhibiting entry, the added cysteine gave the peptide the capacity to inactivate virions in solution and induce a state of resistance to infection in cells pretreated with the peptides. The peptide composed entirely of D-amino acids (TAT-CD) was equally as effective as the L-amino acid version, indicating that chirality is not critical (9). The TAT-C peptide has previously been shown to have low toxicity both in vitro and in vivo (1).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…27,28 On the other hand, amino acids have emerged as important building blocks for the synthesis of a range of different compounds. [29][30][31] Moreover, the interest on the biological and medicinal properties of chalcogen amino acids has also been increasingly appreciated, mainly due to their antioxidant, 32 antitumor, 33 antimicrobial, 34 and antiviral 35 properties.…”
Section: Introductionmentioning
confidence: 99%